Do engineers believe in spontaneous order? The case of Jacques Rueff - Vincent Carret (Duke University, Center for the History of Political Economy (CHOPE), 2023)
In the 1950s, Jacques Rueff's references to social order seem pretty clear: it is not a spontaneous phenomena. Although Rueff is generally seen as a liberal economist, this has prompted commentators to see in his approach something more artificial than Hayek's own ideas on social order. Hayek himself was befuddled by Rueff's reflections on social order and spontaneous emergence. This present paper seeks to explore what Rueff meant by spontaneity, by going back to the scientific context of the 1950s, when Rueff began to reframe his ideas on social order through the lens of cybernetics. Exploring Rueff's cybernetic moment enlightens us on the context in which he developed his thoughts on social order, and what liberalism was for the French economist.
Keywords: B20; B25; B31; B53; 330; Jacques Rueff; cybernetics; spontaneous order; F. A. Hayek